Innovative Public Procurement Failure: A Case Analysis from Poland - Woźniak, Monika (Journal of Public Governance, 2023)
Objectives: The rising popularity of Innovation Public Procurement (IPP) raises questions about its effectiveness as a tool for transformative policies, including governance levels, coordination, and strategic development. The purpose of the article is to explore the failure of governance in a Polish IPP to present how IPP guidelines are implemented empirically. Research Design & Methods: The research article presents conclusions from the case study of first large-scale trial of public procurement procedure with respect to an innovative partnership in Poland. Findings: The case is a rarely analysed example of policy failure and shows that ignoring stakeholders’ needs, timeline constrains, and market capacity can result in policy failure. Programme history highlights that proper risk analysis and adaptation to the market context can prevent programme failure. Implications/Recommendations: The article opens up a field for considering what steps are crucial in formulating IPP, especially in country with lower level of innovativeness. The analysis leads to the main conclusion that transformative policy frameworks using demand-pull tools need to be embedded in the market realities and capabilities of national innovation systems. Contribution/Value Added: The article strives to fill a gap in the literature on implementing transformational innovation policies in peripheral countries, which are less frequently described. The other contributions refer to merging the DARPA’s approach and IPP. Article classification: research article Keywords: innovation policy, innovation public procurement, policy failure JEL classification: O380